Vehicle Routing under Consideration of Driving and Working Hours A Distributed Decision Making Perspective - Meyer, Christoph Manuel (Gabler, 2011)
In April 2007 new legal rules concerning the driving and working hours of truck drivers have become valid in all member countries of the European Union. In the study of Christoph Manuel Meyer the dispatchers' problem of combined vehicle routing and break scheduling is modelled and solved using an efficient heuristic solution algorithm. Special attention is given to the distributed decision competences between dispatchers and drivers, which are usually encountered in practice. Finally, strategies for including the legal rules in the dispatching process are suggested, which can easily be implemented by freight forwarding companies in practice.